2010
DOI: 10.1007/s00415-010-5840-9
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of exhausted cerebral vasoreactivity in carotid occlusion: benefit of statins?

Abstract: In internal carotid artery occlusion (ICAO), a spontaneous increase of cerebral vasoreactivity (CVR) may occur over time. Statins are known to increase CVR. We analyzed the influence of statin treatment and other cofactors on CVR improvement in patients with ICAO. Sixty-six patients with ICAO were reexamined after 15 ± 6 months. CVR in both middle cerebral arteries was assessed by transcranial Doppler and inhalation of 7% CO(2). Pre-defined cut-off values were used to define exhausted CVR. Cofactors analyzed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…28 The effects of statins on cerebral hemodynamics and CA in human studies has previously been reviewed and summarised by Giannopoulos et al 29 Chronic statin therapy improved cerebrovascular function in eight out of ten clinical studies. For studies in patients with cerebrovascular disease there was one study with improvement in CBF 30 and four studies that demonstrated improvements in CVR, [31][32][33][34] whilst some did not improve CBF 35 or CVR. 36 Interestingly, the cerebrovascular effects of statin appeared to be greater in patients who likely have impaired vasomotor reactivity.…”
Section: Statinsmentioning
confidence: 99%
“…28 The effects of statins on cerebral hemodynamics and CA in human studies has previously been reviewed and summarised by Giannopoulos et al 29 Chronic statin therapy improved cerebrovascular function in eight out of ten clinical studies. For studies in patients with cerebrovascular disease there was one study with improvement in CBF 30 and four studies that demonstrated improvements in CVR, [31][32][33][34] whilst some did not improve CBF 35 or CVR. 36 Interestingly, the cerebrovascular effects of statin appeared to be greater in patients who likely have impaired vasomotor reactivity.…”
Section: Statinsmentioning
confidence: 99%
“…An increase in CVR has been described after statin treatment in patients with small vessel disease but is unclear if this effect is also seen in patients with internal carotid artery occlusions (ICAO). Reinhard et al [14] investigated the presence of spontaneous improvement of an exhausted CVR in patients with ICAO and the potential influence of statin treatment and other cofactors on this phenomenon. They analyzed data from 66 patients included in a prospective observational cohort study on cerebral hemodynamics in severe carotid artery stenosis and occlusion.…”
Section: Brain Hemodynamicmentioning
confidence: 99%